(untitled) (Academicia Globe: Inderscience Research, 2022)
This article discusses the history of the origin of cultivated plants, the possibility of creating fertile varieties, as well as fertile and disease and pest-resistant hybrids, using the wild ancestors of cultivated plants in selection work.